2011
DOI: 10.1177/0218492310394465
|View full text |Cite
|
Sign up to set email alerts
|

Intramural esophageal bronchogenic cysts

Abstract: Bronchogenic cysts are most frequently located in the middle mediastinum near the carina. Esophageal bronchogenic cysts are extremely rare. An intramural esophageal bronchogenic cyst was successfully resected from a 51-year-old man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…Early surgical intervention is obviously less traumatic for both patient and surgeon and guidelines for timing need to be established by further research on the natural history of bronchogenic cyst. Transbronchial aspiration and transesophageal needle aspiration have been reported as alternatives to surgical excision, but we do not recommend these procedures because of high risks for recurrence [5,19,21]. Fig.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Early surgical intervention is obviously less traumatic for both patient and surgeon and guidelines for timing need to be established by further research on the natural history of bronchogenic cyst. Transbronchial aspiration and transesophageal needle aspiration have been reported as alternatives to surgical excision, but we do not recommend these procedures because of high risks for recurrence [5,19,21]. Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Moz et al [19] reported that MRI is valuable for demonstrating the size and shape of a cyst and in determining its position in relation to other structures. Because bronchogenic cysts mostly contain large amounts of proteinaceous material or blood, cysts have high signal intensity on both T1-and T2-weighted images [5,19]. Contrast examinations of the esophagus have also been recommended to assess communication with surrounding structures that may be seen as a smooth luminal indentation, or evidence of extrinsic compression [5,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations